UAV-based high-throughput phenotyping to discriminate barley vigour with visible and near-infrared vegetation indices. Issue 15 (18th August 2018) - Di Gennaro, Salvatore Filippo; Rizza, Fulvia; Badeck, Franz Werner; Berton, Andrea; Delbono, Stefano; Gioli, Beniamino; Toscano, Piero; Zaldei, Alessandro; Matese, Alessandro
ABSTRACT: In the context of plant breeding, high-throughput phenotyping is an assessment of plant phenotypes on a scale and with a level of speed and precision not achievable with traditional methods, through the application of emerging technologies such as automation and robotics, new sensors, and imaging technologies (hardware and software). In the present work, high-resolution digital images have been acquired with an unmanned aerial vehicle (UAV) prototype platform on an experimental phenotyping barley field. Six vegetation indices generated from the red–green–blue and near-infrared-based images were calculated for 912 experimental barley plots and provided high correlation with the indices determined from hyperspectral data taken at the ground (gt); the indices performance in discriminating the vigour of genotypes was finally assessed.